The System of Internal Control as a Factor in the Integration of the Strategic and Innovation Dimensions of a Company’s Development - AKHMETSHIN, Elvir Munirovich (Journal of Advanced Research in Law and Economics, 2017)
This research study owes its relevance to the increasing practical significance of control amid intensifying recessional trends in the economy. Putting together an efficient system of internal control is becoming one of the crucial factors for the successful development of companies and boosts in their competitiveness. The system of internal control ought to be aimed at fulfilling both the company’s current and strategic objectives for its business activity. This paper employs a set of general scholarly methods of research, like analysis and synthesis, search for cause-and-effect relationships, linking logical and historical processes, and the laws of dialectics. The author also draws upon the theory of innovative development, the theory of scientific management, and an institutional approach. Control is viewed as one of the most significant functions of management. It is both subordinate and dominant in relation to management’s other functions. The paper provides an insight into the fundamental principles underlying the process of putting together the company’s system of internal control. Control is seen as a condition for being able to fulfill the company’s strategy and as a factor for its innovative development. The author suggests that, to boost the efficiency of control, it helps to employ a matrix organizational-management structure based on frame-based (event) data processing. To ensure the integration of strategic and innovation objectives for development, it helps to employ the COSO ICIF and ISO 9001:2015 international management standards. Putting in place control activities based on the BSC and KPI systems will help meet the requirements of international standards and ensure the flexible (adaptive) work of the system of internal control. The author identifies some of the key characteristics of companies’ system of internal control crucial to resolving their strategic and innovation objectives for development. The paper also puts forward a set of recommendations for enhancing companies’ system of internal control under today’s conditions.